Recurrence after ESD curative resection for early gastric cancer - Ayako Kamiya; Hitoshi Katai; Kenichi Ishizu; Takeyuki Wada; Tsutomu Hayashi; Sho Otsuki; Yukinori Yamagata; Takaki Yoshikawa; Shigeki Sekine; Tomohiko Nishi; Yuka Kawasaki; Takafumi Ito; et al. (Surgical Case Reports)
Abstract Background Endoscopic submucosal dissection (ESD) is gaining ground as a minimally invasive treatment for early gastric cancer (EGC) that has a negligible risk of lymph node metastasis. According to the 5th edition of Japanese gastric cancer treatment guidelines, annual or biannual follow-up with endoscopy is recommended, but follow-up with abdominal ultrasonography or computed tomography (CT) for surveillance of metastases is not recommended after the eCuraA resection. However, we experienced a case of lymph node recurrence following ESD resulting in eCuraA. Case presentation A 76-year-old female received ESD for EGC in a previous hospital 4 years ago. Pathological findings were tub1, 30 mm, T1a (M), UL0, Ly0, V0, pHM-, pVM- (eCuraA) according to the 15th edition of Japanese Classification of Gastric Carcinoma. Follow-up esophagogastroduodenoscopy revealed submucosal tumor, which was suspected as a swollen lymph node by CT and endoscopic ultrasound fine-needle aspiration revealed the recurrence of gastric cancer. We performed total gastrectomy with D2 lymph node dissection. Postoperative pathological examination revealed no local recurrent tumor at the ESD site in the stomach. Swollen lymph node was diagnosed as metastasis and lymph node metastasis was limited near the cardia. Conclusion This case provides valuable information about tumor with a minimum poorly differentiated adenocarcinoma component may develop lymph node metastasis even satisfying the guidelines criteria for curative resection.